Development of coating material by incorporating curcumin-loaded zein nanoparticles to maintain the quality of mango (Mangifera indica L. cv. Nam Dokmai) - Thanida Chuacharoen; Cristina M. Sabliov (Journal of Agriculture and Food Research, 2022)
Anthracnose caused by Colletotrichum gloeosporioides is a major postharvest disease that reduces the shelf life of mango (Mangifera indica L. cv. Nam Dokmai), an indigenous crop of Thailand. Curcumin, a substance in turmeric, has antimicrobial activity, which is hypothesized to be enhanced in the form of nanoparticles. In this research, curcumin-loaded zein nanoparticles (CZNP) were synthesized using a liquid-liquid dispersion method and were incorporated into zein coating material. The effect against C. gloeosporioides was evaluated relative to curcumin and zein mixture solution (CZ) as a control. The results showed that the solution of free curcumin at 100 μg/ml (CZ100) was less effective compared to when curcumin was entrapped in zein nanoparticles at the same amount (CZNP100), which was more effective at inhibiting the mycelial growth of C. gloeosporioides. It was consistent with the study of disease severity when the curcumin in both forms was mixed in zein coating materials and applied to mangoes. The disease severities of inoculated mangoes treated with CZNP and CZ were significantly retarded (25.93% and 39.79%) compared to the uncoated mangoes (64.13%) after 9 days of storage. Subsequently, their effect also prolonged the postharvest quality of mangoes after 9-day storage in terms of delayed color change and loss of weight and firmness. These results indicated that functionalized curcumin-loaded zein nanoparticles added in a biodegradable zein coating significantly suppressed anthracnose disease severity in mango fruit, providing a promising strategy for disease control in mango fruit.